Tafsir Feminisme Perspektif Amina Wadud - Maelina Putri Maratu Solihah; Muhammad Ahmad Mumtaz Muizza; Muhammad Dzikri Maulana; Andi Rosa (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study discusses the position of women in the creation of humankind based on Amina Wadud's feminist hermeneutics perspective as an effort to critique classical interpretations of the Qur'an that tend to be gender biased. For centuries, the tradition of interpretation dominated by male exegetes has shaped a theological understanding that places women in a subordinate and inferior position, especially in the narrative of human creation. Amina Wadud, as one of the contemporary Muslim feminists, offers a feminist hermeneutics approach that emphasizes the importance of historical context, linguistic analysis, and women's experiences in understanding the Qur'anic text in a more fair and comprehensive manner. This study specifically examines Wadud's interpretation of QS. An-Nisa 'verse 1, which states that humans were created from nafsun wahidah (one soul). Wadud asserts that this concept indicates the equality of origin between men and women, thereby rejecting the patriarchal view that women were created from men's ribs as second-class beings. The research method used was qualitative with a literature study approach, through analysis of Amina Wadud's works and relevant academic literature. The results of the study show that Wadud's feminist hermeneutics not only serves as a critique of classical interpretations that are laden with patriarchal bias, but also provides a strong theological basis for the recognition of gender equality in Islam. This approach opens up space for women to play an equal role in the social, political, and religious spheres. Thus, Amina Wadud's thinking contributes significantly to building a more inclusive, egalitarian, and gender-equitable understanding of Islam in accordance with the universal values of the Qur'an.